Assessment of Safe Thickness of Parting Strata and Optimal Capacity of Goaf Edge Supports for Safer Extraction of Developed Coal Pillars Under Soft Cover - Sahoo S.K.; Singh G.S.P. (My University, 2025)
The underground coal mines under the soft cover require a phenomenal understanding of strata control to maintain mine stability for overburden load transfer during progressive depillaring operations in prevailing Indian geo-mining conditions. This paper highlights the Indian underground mines under soft cover conditions, which have challenges leading to instability of the parting strata due to uncontrolled load transfer of the dead load at the time of commencement and continuance of the working operations. A numerical modelling study was conducted in this work to assess the strata and support behaviour during progressive extraction of the developed pillars under varying thicknesses of the parting strata (PS) and the soft cover (SC) at the cover depth of 150–350 m. The modelling results were analysed to develop an approach for estimating the safe thickness of PS for a controlled and sustainable load transfer. It considered the maximum allowable convergence at the goaf edge (MACGE), which was further confirmed by the trend of the peak settlement rate (PSR) and the location of failure of the parting strata during the progressive depillaring. The laboratory investigation and numerical modelling of the prevailing soft cover condition in Kuiya Colliery were performed, and the modelling results of the parametric study were validated using the results of Kuiya Colliery and other relevant published data. The optimum capacity of the goaf edge support has also been estimated for the safe PS and the MACGE to ensure safe extraction in the given geo-mining conditions. © Society for Mining, Metallurgy & Exploration Inc. 2025.